Blockchain and distributed ledger technologies in the humanitarian sector - Giulio Coppi; Larissa Fast (Overseas Development Institute (ODI), 2019)
Blockchain and the wider category of distributed ledger technologies (DLTs) promise a more transparent, accountable, efficient and secure way of exchanging decentralised stores of information that are independently updated, automatically replicated and immutable. The key components of DLTs include shared recordkeeping, multi-party consensus, independent validation, tamper evidence and tamper resistance. Building on these claims, proponents suggest DLTs can address common problems of non-profit organisations and NGOs, such as transparency, efficiency, scale and sustainability. Current humanitarian uses of DLT, illustrated in this report, include financial inclusion, land titling, remittances, improving the transparency of donations, reducing fraud, tracking support to beneficiaries from multiple sources, transforming governance systems, micro-insurance, cross-border transfers, cash programming, grant management and organisational governance. This report, commissioned by the Global Alliance for Humanitarian Innovation (GAHI), examines current DLT uses by the humanitarian sector to outline lessons for the project, policy and system levels. It offers recommendations to address the challenges that must be overcome before DLTs can be ethically, safely, appropriately and effectively scaled in humanitarian contexts.
Keywords: 330